2017
DOI: 10.25077/jpi.19.3.170-177.2017
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Growth Traits of Simmental Cattle in Balai Pembibitan Ternak Unggul-Hijauan Pakan Ternak (BPTU-HPT), Padang Mengatas, West Sumatra, Indonesia

Abstract: This study is proposed to determine the heritability of growth traits of Simmental cattle in BPTU-HPT Padang Mengatas, West Sumatra. Data were collected by observations and measurements of the cattle in the field, completed by the secondary data from BPTU-HPT recorded from 2010 to 2016. Data for heritability were collected from 455 offsprings belonged to 15 sires. Weight and body size are two parameters used to estimate the heritability and breeding value, the heritability was analyzed between weaning and year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Several studies showed that weaning and yearling weight had high value of h 2 in Indonesian beef cattle such as Bali (Kaswati et al, 2013;Gunawan and Jakaria, 2011), Ongole grade (Hartati et al, 2015), Simmental (Putra et al, 2017), Aceh (Sari et al, 2016) and Brahman cross (Duma and Tanari, 2008). In addition, weaning and yearling show high category of r g in Indonesian beef cattle such as Bali (Prajoga and Talib, 2008), Madura (Karnaen, 2008) and Simmental (Suhada et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that weaning and yearling weight had high value of h 2 in Indonesian beef cattle such as Bali (Kaswati et al, 2013;Gunawan and Jakaria, 2011), Ongole grade (Hartati et al, 2015), Simmental (Putra et al, 2017), Aceh (Sari et al, 2016) and Brahman cross (Duma and Tanari, 2008). In addition, weaning and yearling show high category of r g in Indonesian beef cattle such as Bali (Prajoga and Talib, 2008), Madura (Karnaen, 2008) and Simmental (Suhada et al, 2009).…”
Section: Introductionmentioning
confidence: 99%